ETIKA KONSUMSI DALAM PERSPEKTIF EKONOMI ISLAM - Andi Bahri S. (Hunafa: Jurnal Studia Islamika, 2014)
This paper deals with  consumption  behavior  in society; how to consume as recommended by Islam;  and  how  should  consumption  behavior in the view of  Islamic economics. Based on the results of the analysis, we concluded as follows: 1) Consumption behavior should pay attention to the aspects of the categories of needs asprimary needs, secondary needs and tertiary needs  in accordance with the spirit of al-maqāṣd al-syarī’ah. In the view of  Islam, consumption behavior should avoid isrāf and tabżīr behavior in using their income to meet their life needs. In the aspect of comsuming any kind of food, the Muslims should  always comsume the  halal   and  the  toyyib  food.  Consumption behavior  in  Islamic  economics aims at achieving both the aspect of material and the aspect of  spriruality,  these two aspects will be achieved by maximizing the value of the use of each item in consumption.Kata kunci:  Perilaku konsumsi, kebutuhan, keingingan, ekonomi Islam